Usefulness of unwinding the colonoscope shaft loop via the universal cord for colorectal endoscopic resections - Taiji Yoshimoto; Hiroshi Takihara; Ryuichi Yamamoto (Clinical Case Reports)
Key Clinical Message The colonoscope shaft loop can be unwound by establishing a loop in the universal cord of the colonoscope to maintain the same endoscopic view during colorectal endoscopic resections.